Konseling Behavioral dengan Teknik Desensitisasi Sistematis Untuk Mereduksi Anxiety - Oktavia, Anisa; Kasih, Fitria; Usman, Citra Imelda (Jurnal Bimbingan dan Konseling Pandohop, 2024)
The purpose of this study was to examine the effectiveness of behavioral counseling with systematic desensitization techniques to reduce anxiety in students. This study uses a quantitative experimental method with a One Group Pretest and Postets research design, while the sampling technique is done with total sampling technique. The instrument used is a questionnaire, while for data analysis using percentage intervals and t test analysis. The result of this study is a decrease in students' anxiety behavior after participating in behavioral counseling services with systematic desensitization techniques. It can be seen that the average level of anxiety in students before being given behavioral counseling services using systematic desensitization techniques is 191 with the average level of anxiety in students after being given behavioral counseling services using systematic desensitization techniques is 125. So it can be concluded that behavioral counseling with systematic desensitization techniques has succeeded in reducing anxiety in class X phase E11 students at SMAN 1 Gunung Talang. Based on the results of the research that researchers have done, it can be said to be successful, but further researchers can expand the sample and use other techniques in reducing anxiety.